Property Tax in Anglophone Africa : Issues and Constraints - Keith, Simon (World Bank, Washington, DC, 2012)
All the countries in Anglophone Africa share a common history of British colonialism. Many of the administrative practices and laws are similar. There must have been a model set of legal clauses for property tax produced in Whitehall for the colonial administration to use and adapt to local conditions. The shadow of it still persists in similar phrases found in the laws of many different countries. But the laws and local conditions are not identical for all countries. The paper previewed in this article is a practical manual which discusses legal issues; the process of setting up a valuation office; property tax collection; management issues related to the day-to-day running of the valuations office; and making property tax politically acceptable. The central core of the book, however, gives practical instructions on how to get a revaluation done. The book also touches upon computers, privatization, training and skills, and buoyancy. It concludes with a list of criteria by which success may be measured.